Multi-photon processes and spectroscopy (World Scientific, 2011)
Includes bibliographical references.; Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.; Quỹ Châu Á